Chile : Financial Sector Assessment Program-Technical Note on Crisis Management and Bank Resolution. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
Chile has a large and well-developed financial system, compared with the rest of Latin America. The market is well integrated into the global financial system, with Chilean firms investing in foreign financial assets, either directly or via institutional investors, and foreigners participating in the Chilean market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Chile